Dashnaxion and the concept of Armenian national government - A Mazinani; A Shekofte (پژوهش های تاریخی, 2013)
Dashnaxion (Dashnaktsutyun) party, together with some other Armenian parties that all had great excitement to set Armenians free, was established during the last years of 1880s. Considering the dominance the party obtained over the political life of Armenians in less than 10 days, it was not surprising that it can authorize the country in May 28, 1918, after Armenia declared its independence. Dashnaxionrequired theoretical background on Armenian independent government to be able to perform its political role. The present article, using a descriptive explanation, reveals that the party lacked any coherent and explicit theory on national government from 1890 to 1918, and during the time, in five separate periods it sometimes became close to the concept “national government” and sometimes far from that concept. Finally, after the independence of Armenia, the party was forced to lead the new government without previous preparation.